Solving the mysteries of urate transport: structural insights into GLUT9 and URAT1 - Mei Wang; Shujing Xu; Xiaoyu Shi; Edeildo Ferreira da Silva-Júnior; Peng Zhan (Acta Materia Medica)
Recent groundbreaking advances in the structural biology of the glucose transporter 9 (GLUT9) and urate transporter 1 (URAT1) have provided critical insights into the molecular mechanisms underlying urate recognition and transport. Using cryo-electron microscopy (cryo-EM), researchers have elucidated the structures of these transporters at high resolution, thus revealing their substrate preferences and interactions with inhibitors. Several studies have highlighted the potential of specific inhibitors, such as apigenin for GLUT9, and have demonstrated the role of chloride-mediated inhibition in URAT1 function. These findings provide an excellent starting point for developing targeted therapies for hyperuricemia and gout, to enable the design of more effective and selective drugs in the future.